## Expanding (x+1)(x+3)(x-4) into Standard Form

To express the polynomial (x+1)(x+3)(x-4) in standard form, we need to perform the necessary multiplications and combine like terms.

### Step 1: Multiply the first two factors

Let's start by expanding the product of (x+1) and (x+3):

(x+1)(x+3) = x(x+3) + 1(x+3)
= x² + 3x + x + 3
= **x² + 4x + 3**

### Step 2: Multiply the result by the third factor

Now, we multiply the result from Step 1, (x² + 4x + 3), by (x-4):

(x² + 4x + 3)(x-4) = x²(x-4) + 4x(x-4) + 3(x-4)
= x³ - 4x² + 4x² - 16x + 3x - 12
= **x³ - 13x - 12**

### Conclusion

Therefore, the standard form of the polynomial (x+1)(x+3)(x-4) is **x³ - 13x - 12**.